Witchcraft in the Lithuanian Village Community in the Beginning of the 21st Century (on the Folklore Fieldwork Material) - Būgienė, Lina (Tautosakos darbai, 2024)
The article is based on the materials collected during four folklore fieldwork sessions that took place in the different regions of Lithuania in the first decade of the 21st century. The aim is to present popular beliefs and legend-like narratives related to harmful magic that are still preserved in the Lithuanian villages, and the informants’ attitudes towards them. The point of departure for the analysis was the category of the “strange people” discussed by Norbertas Vėlius in his book “Mythical Beings of the Lithuanian Legends”. However, as folklore data from the beginning of the 21st century reveals, some subcategories of these “strange people” discerned in the book are by now totally extinct from the living tradition (like werewolves or “soul-seers”), while others, including witches, wizards, evil-eyed people and partly, charmers, have inextricably merged together. Thus the article focuses on a general, overlapping phenomenon, namely witchcraft. Having taken into account the universal character of this phenomenon, the author strives to discern its peculiarities that are typical to the Lithuanian village communities. Using comprehensive analysis of the figure of the neighborhood witch developed by the Slovenian folklore researcher Mirjam Mencej, the author discusses typical features and activities of this quasi-mythical being, as reflected in the Lithuanian fieldwork material, i. e. harming of livestock, love magic, curses, and evil-eye. The neighborhood witch is perceived as acting within the framework of the opposition between one’s own and other, moreover, representing both sides of it. Precisely this, according to the author, induces great fear and anxiety that other members of the community exhibit towards this figure, at the same time resulting in its exceptional persistence and longevity.